Gender Roles (Statuses) and Indonesian Wowan - Ernita Daulay (UIN Sumatera Utara, 2017)
A gender role is a set of societal norms dictating the types of behaviors which are generally considered acceptable, appropriate, or desirable for people based on their actual or perceived sex or sexuality. Gender roles are usually centered on conceptions of femininity and masculinity,although there are exceptions and variations. The specifics regarding these gendered expectations may vary substantially among cultures, while other characteristics may be common throughout a range of cultures. There is ongoing debate as to what extent gender roles and their variations are biologically determined, and to what extent they are socially constructed.Islam looks at the woman as an equal, mature and capable partner of a man, without whom a family cannot exist and teaches that men and women are all the creation of Allah, existing on a level of equal worth and value. In some societies women are treated according to ancestral customs and tribal tradition, but in Islam they are treated with full respect and honor. Islam preserves women's honor and dignity, and requires that she must be treated with respect and honor. Her femininity should not be exploited in any way, rather she is to be regarded and treated as human individual whose sexuality does not enter into her relationship with any person other than her husband. In Islam marriage cannot take place unless the female freely agrees to it and a dowry is given to her. Islam puts priorities for the husbands and wives. The responsibility for providing for the family is on the husband, while the responsibility to care for the house and raising the children is on the wife. These are the main priorities, but cooperation between the husband and the wife is required and highly recommended. For both males and females, Islam requires that they wear proper, decent, modest, and clean clothes. Muslim women also are instructed by Allah in the Quran to wear as a minimum Hijab (head covering). At home, with her immediate family like her husband children, brothers, uncles, grandfathers and other males (family members who are forbidden to them to marry her), and with other women, a Muslim woman may take her outer garments off, and be free to beautify herself as she wants.